2021
DOI: 10.1109/tvt.2021.3078002
|View full text |Cite
|
Sign up to set email alerts
|

EE Optimization for Downlink NOMA-Based Multi-Tier CRANs

Abstract: Non-orthogonal multiple access (NOMA) is increasingly becoming very attractive in cloud radio access networks (CRANs) to further boost the overall spectral efficiency, connectivity and, capacity of such networks. This paper addresses optimizing the energy efficiency (EE) for the downlink of a NOMAbased two tiers CRAN. The stochastic geometry represented by Poisson Point Process (PPP) distribution is used to decide the number and locations of the base stations (BSs) in each tier within the coverage area. A nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…At S, the messages of users are combined in an SC information signal with different power levels according to the users' channel gain 2 and the R receives this information signal in the first phase. Thus, the received information signal by the R node is given as…”
Section: System Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…At S, the messages of users are combined in an SC information signal with different power levels according to the users' channel gain 2 and the R receives this information signal in the first phase. Thus, the received information signal by the R node is given as…”
Section: System Modelmentioning
confidence: 99%
“…Non-orthogonal multiple access (NOMA) is widely renowned for increasing the number of users and improving spectral efficiency in next-generation wireless networks [1][2][3]. Besides, NOMA can be easily integrated with other physical layer schemes.…”
Section: Introductionmentioning
confidence: 99%
“…Several existing literature works, i.e., refs. [1,2,[4][5][6][7][8][9][10][11][12] have explored different aspects of NOMA potential and their outcomes have approved its effectiveness, especially against its orthogonal predecessors. NOMA has proven its vitality to be adapted as a future air interface as a stand-alone, or even in combination with existing techniques such as multi-input multi-output (MIMO) [6,13,14] and device-to-device (D2D) communications [4,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…NOMA was also presented as a delivery approach for multicast systems [6], NOMAbased cloud-radio access networks (CRAN) [7], etc., most of those works have showed that expressing a multiuser NOMA system is not simple and requires a complex approach specially to design the SIC decoding process. Therefore, some researchers investigated user pairing and user clustering as a mean to handle this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Based on which, the cellular spectrum is shared by choosing the D2D source that offers the highest achievable SINR. In addition, the optimization NOMA based CRAN is investigated by [7] in terms of the achievable energy efficiency. The authors proposed a number of power allocation assignments and addressed the effectiveness of NOMA-CRAN combination in a multi-tier network.…”
Section: Introductionmentioning
confidence: 99%